Nation building and the ‘struggle for Afrikaans’ under the new South African ‘rainbow’ - F. Jansen van Rensburg (Koers : Bulletin for Christian Scholarship, 2003)
Although the geographical, technological and economic aspects of the South African nation have a reasonably stable basis, the socio-cultural aspect is not only contested, but has since 1994 led to new movements and public debates regarding the recognition of the position of some categories/minorities and their rights in the newly-created democratic dispensation. It would not be correct to assume that all these ‘new’ movements and voices are of a centrifugal nature and therefore indicative of potentially separatist tendencies. Whereas most of the evolution and history of ‘Afrikaans’ stemmed from its proponents’ opposition to the imposition of English and its imperialist backing, the current debate is about Afrikaans being displaced and relegated to a lowly position by an Englishspeaking black-majority government. Surveying the nature and context of this public debate on the ‘position of Afrikaans’ will broaden the understanding of contemporary ‘nation building’ in South Africa. Again, social scientists could endeavour to comprehend culture ‘in the making’ as created by some of the ‘imaginative’ Afrikaans-speaking participants and the implications of this discourse for nation building and competition.